The lost history of stars : a novel - Boling, Dave (Algonquin Books of Chapel Hill, 2017)
"From a forgotten moment in history comes an inspiring novel about finding strength and courage in the most unimaginable places. Fourteen-year-old Lettie and her family are Afrikaners, Dutch settlers in turn-of-the-century southern Africa. When the British Empire wages a brief but brutal two-year war against them, Afrikaner forces will lose thirty-five hundred soldiers, but the toll on Dutch women and children will be eight times greater. Now a footnote, this period in history bears one particularly abhorrent distinction: the use of concentration camps three decades before Hitler. More than twenty-six thousand Dutch women and children will have died of disease and starvation in British concentration camps by the war's end. Taken from their farm and forced into one such camp, Lettie and her family fight to survive in the face of unimaginable conditions. Brave, defiant Lettie longs to be a writer. Enriched by fond memories of stargazing with her grandfather before the war and emboldened by her mother's strength in the face of so much hardship, Lettie is a courageous heroine who refuses to be bowed by adversity. Inspired by Dave Boling's grandfather's own experience as a soldier during the Boer War, The Lost History of Stars is carefully researched, richly drawn, and unforgettable"--